Bahan edaran dan organisasi media : kajian di Utusan Sarawak dan RTM Sarawak - Dayang Nor Hajjah, Binti Haji Awang Daud (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study is about media materials received by RTM Sarawak and Utusan Sarawak in November and December 2012 from different individual or representative of an organization whether writen by public relations officer or non public relations officer. This study has the objective to identify the types as well as to analyze the content of materials received by two media organizations in the study period. COPR model used in the discussion of the theory and content analysis was used as a method to analyze the materials that have been received by a local Sarawak newspaper and a national TV and radio stations in Sarawak. These materials are divided into two major categories, namely statement to the media and the press releases. Organizations were more likely to send their materials to the electronic media as it has broader broadcast nationwide compared to the local daily newspapers which have limited circulation in the state. The study also found that most of the content of these materials were writen according to guidelines suggested by experts in the field of public relations. The results also improve the COPR model in terms of public relations officer and non public relations officer as an information provider, role of the media as a channel of information to the public and some of public are also a writer who provides information to the media.